Peranan Teknologi Dan Sistem Informasi Pada Manajemen Hulu Hilir Bidang Agroindustri - Utama, Ditdit N. (Lembaga Penerbitan Universitas Esa Unggul, 2007)
Information Technology and Information System, and then they called as information system, have growth rapidly. Almost in every field of business they have good position, both as supporting tool and strategic tool to win the competition. In agro industry, Information System has important rule. It has rule in purchase system, distribution system, inventory system up to marketing system. In this paper, these rules will be explained broadly.Keywords: Information Technology,Information System, Agro Industry